Homicide Hot Spots in Chicago: Examining Spatiotemporal Patterns Longitudinally Across Police Beats - Gullion, Christi (Crime & delinquency, 2024)
Prior research on crime hot spots has been mostly concerned with the analyses of cross-sectional data or short-term aggregations. Less research, however, has conducted longitudinal analyses on homicide hot spots and their dynamic behavior over time. The current study assessed 5?years of Chicago homicides (2016?2020) by police beats to explore how hot spots of homicides behave, with specific attention to durability. We find that Chicago homicides spatially and temporally cluster, with analysis suggesting the emergence of seasonal, short term, and long term ?durable? hotspots in Chicago. Policy implications such as police interventions and community policing and problem-solving opportunities are discussed.